Slow breathing training reduces resting blood pressure and the pressure responses to exercise - Jones, C. U; Sangthong, B; Pachirat, O; Jones, D. A (Physiological research, 2015)
Slow breathing training reduces resting blood pressure, probably by modifying central autonomic control, but evidence for this is lacking. The pressor response to static handgrip exercise is a measure of autonomic control and the aim of this study was to determine whether slow breathing training modulates the pressor responses to exercise of untrained muscles. Twenty hypertensive patients trained for 8 weeks, 10 with unloaded slow breathing (Unloaded) and 10 breathing against an inspiratory load of 20 cm H(2)O (Loaded). Ten subjects were untrained controls. Subjects performed a 2 min handgrip pressor test (30 % MVC) pre- and post-training, and blood pressure and heart rate (HR) were measured before the contraction, at the end and following 2 min recovery. Resting systolic (sBP) and HR were reduced as a result of training, as reported previously. After training there was both a smaller pressor response to hand grip exercise and a more rapid recovery of sBP and HR compared to pre-training. There were no changes in the Controls and no differences between the Unloaded and Loaded groups. Combining the two training groups, the sBP response to handgrip exercise after training was reduced by 10 mm Hg (95 % CI: -7, -13) and HR by 5 bpm (95 % CI: -4, -6), all p<0.05. These results are consistent with slow breathing training modifying central mechanisms regulating cardiovascular function.
Keywords: Male; Breathing Exercises; dechová cvičení; Heart Rate; Adult; Hand Strength; Aged; dospělí; mužské pohlaví; senioři; síla ruky; srdeční frekvence; měření krevního tlaku; Exercise; lidé; krevní tlak; ženské pohlaví; Humans; Blood Pressure; Female; cvičení; lidé středního věku; Blood Pressure Determination; Middle Aged